1999
DOI: 10.1161/01.atv.19.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Vascular Endothelial Growth Factor/Vascular Permeability Factor in Atherosclerotic Intimas of Human Coronary Arteries

Abstract: Abstract-Neovascularization is well known to occur in human atherosclerotic plaques; however, its pathophysiological roles, mechanisms, and stimuli in atherogenesis still remain unclear. In this study, 525 tissue blocks of coronary artery tissue obtained at autopsy from 48 patients ranging in age from 20 to 93 years old (meanϮSD, 71Ϯ15 years) were immunohistochemically examined for vascular endothelial growth factor (VEGF) expression in the atherosclerotic intimas. The atherosclerotic lesions were histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 56 publications
6
65
0
Order By: Relevance
“…Intimal neovascularization is a common feature of atherosclerotic disease, correlating with histological alterations 34 and symptoms. 9 Neovascularization density increased in lesions with marked macrophage infiltration of TCFA, 10 lipid-rich lesions, 35 and lesions with intraplaque hemorrhage and rupture.…”
Section: Microchannelsmentioning
confidence: 99%
“…Intimal neovascularization is a common feature of atherosclerotic disease, correlating with histological alterations 34 and symptoms. 9 Neovascularization density increased in lesions with marked macrophage infiltration of TCFA, 10 lipid-rich lesions, 35 and lesions with intraplaque hemorrhage and rupture.…”
Section: Microchannelsmentioning
confidence: 99%
“…27 Intimal smooth muscle cells and macrophages express vascular endothelial growth factor (VEGF) in human atherosclerotic lesions. 28 Experimental studies have shown that arterial injury is associated with increased intimal and medial expression of VEGF, 29,30 increased circulating VEGF, 31 and smooth muscle cell and endothelial cell proliferation in response to VEGF. 32 Neointimal vascularization within stents, noted previously by Brasen et al, 33 colocalizes with oxidative epitopes, iron deposits, VEGF, platelet-derived growth factor-BB, and microhemorrhages.…”
Section: Importance Of Inflammationmentioning
confidence: 99%
“…1,2 VEGF is essential for embryogenesis, wound healing and corpus luteum formation and even deletion of a single allele of the VEGF gene results in embryonic lethality in VEGF-deficient mice. 3,4 Accumulating evidence has revealed that VEGF plays important roles in pathophysiological conditions with neovascularization, and that upregulation of VEGF expression may be associated with hemangiomas, 5,6 diabetic retinopathy 7 and nephropathy, 8,9 atherosclerosis [10][11][12] and rheumatoid arthritis. 13 In addition, VEGF is involved in the proliferation of several types of tumor cells and the administration of monoclonal antibodies (mAbs) against VEGF suppressed the growth of human tumors implanted into nude mice.…”
mentioning
confidence: 99%